PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, PEMANFAATAN SISTEM INFORMASI AKUNTANSI DAN PENGAWASAN KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Yanti, Nanda Saputri; Made, Anwar; setiyowati, Supami Wahyu (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2020)
Research. it aims. for the. knowing. influence. in a manner. partially.and simultaneous influence application. the standard. accounting. government, utilization. the system. information. accounting. and supervision. finance. towards. report quality. finance. the government. area. Population. in this research is. officials. structural and. section staff. financial function in the organization. Device. Regional (OPD) City. Poor. totaled 14. agency with. respondent. 71. Retrieval. the sample. to use. purposive technique. sampling. With. method. data collection. using a questionnaire. Analysis. the data. use analysis. linear regreasi. multiple with. using SPSS version 22. Results. research shows that application. accounting standard. the government. influential. significant to. the quality. local government financial reports, utilization. the system. information. accounting has no effect. towards. report quality. government finance. area, and supervision. financial influence significantly on the quality of local government financial reports. And simultaneous application. government accounting standards, utilization of information systems.accounting, and. financial supervision. significant effect. towards quality. financial statements. the government. area.